Integration of Religious Moderation in Islamic Curriculum to Strengthen Inclusive Religious Literacy and Support SDGs in the Era of Social Polarisation - Ridho, Ali; Kholisol Muhlis, R.; Lailaturrohmah, Lailaturrohmah; Kholifatul Alam, Fihris; Yaacob, Mashitoh (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This study aims to conduct an in-depth analysis of the integration of religious moderation values within the Islamic boarding school (pesantren) education system and its impact on the development of tolerant, inclusive, and peace-oriented student character. The research stems from growing concerns over social polarization and the rise of religious extremism, underscoring the urgent need to reinforce the values of Islam as a religion of compassion (rahmatan lil ‘alamin). A qualitative research approach was employed, utilizing in-depth interviews, participatory observations, and document analysis as the primary methods of data collection. The findings reveal that core values of moderation such as tolerance, non-violence, national commitment, and respect for diversity are holistically embedded within pesantren life through curriculum design, daily religious practices, and exemplary leadership by kyai and teachers. Integration strategies include strengthening lessons in aqidah, fiqh, and ethics, promoting interfaith dialogue, and cultivating an inclusive pesantren culture. The study highlights that pesantren hold strategic potential in shaping a generation of Muslims capable of peaceful coexistence in multicultural societies. However, challenges remain, particularly the influence of transnational ideological currents contrary to the spirit of moderation and the limited capacity of educators to contextualize these values effectively. Therefore, adaptive and collaborative Islamic education policies involving the government, pesantren institutions, and civil society are crucial to reinforce the role of pesantren as the foundation of religious moderation in Indonesia.